Panchayat as development delivery system - the case of West Bengal - Roy, M.N. (1995)
"The article stresses that the panchayat should carry out the development in two ways (1) channelise development in the best possible way with the existing level of organisational ability with active involvement of the people, and (2) strengthen the process of development by development of human resources for better participation and involvement of the people and build up its own capacity as an organisation for planning and implementing various task related to development. This paper analyses the case of panchayat in West Bengal as a development delivery system"
Keywords: Panchayat - India - West Bengal